Lietuvos kalendoriai 1904-1917 metais - Lietuvninkaitė, Nijolė (Knygotyra, 1998)
More favourable conditions were formed for publishing industry after cancellation the printing interdiction in Lithuania. The first Lithuanian printing-houses, book-shops, libraries, schools, societies, publishing houses have been organized in Vilnius, Kaunas, Seinai and other places. Demand for books have increased for enlightenment purposes. In 1904–1917 was predominance of popular science and training literature in publication of books. Lithuanian calendars were published in large editions (approximately 15 000 copies). There was the largest circulation in the book market. There have been published more than 40 titles of calendars in this period. The most important publishers have lived in Vilnius and Kaunas. The half of all Lithuanian calendars’ production belongs to Vilnius publishers. These calendars have been issued by J. Zawadzki and M. Šlapelienė book-shops, the editorial board of the newspaper „Lietuvos ūkininkas”, publishing houses „Šviesa” and „Žinynas”, private publishers J. Rinkevičius, A. Rucevičius and the others. Five societies in Kaunas (St. Kazimieras, Organists of St. Grigalius the Great, Soberness and so on) have issued the calendars. Also the calendars have been issued in Seinai, Panevėžys, Biržai and other places. The First World War stopped or temporarily suspended the publishing activities. The issue have been renewed in the year of German occupation. The famous Lithuanian writers, historians, economists, agronomists, lawyers have been contributing to these calendars. The calendars have been popularizing fiction, helped for acquiring some knowledge of Lithuanian history, natural sciences, agriculture and medicine. Various readers with different views and development could make one’s choice. In 1904–1917 Lithuanian calendars have been attached to information and educational work. They kept a traditional structure (a calendar and appendix), but their pithiness and informativeness had become more significant. Many readers have been satisfied with Lithuanian calendars, which had been devoted to the farmers, pupils, intellectuals and the broad public. Plenty of press reviews have confirmed the great importance and popularity of calendars among the people. These calendars are useful nowadays for the book scientists. They give various news and facts about Lithuanian press, libraries, bibliophilic societies, reading, book-shops in 1904–1917.